Potencial do RAPD e de microssatélites para estimar distâncias genéticas em milho pipoca (Zea mays L.) - Leal, Ausileide Alves (2008)
Molecular markers RAPD and SSRs loci have been empbyed to estímate and characterize the genetic divergence between 10 S7 endogamic popcorn strains and evaluate the consistency of information from the above-mentioned markers. Primers efficiency for RAPD reached 10.84%. One hundred and twenty-six amplified primers were produced from the nine selected primers. Since 22 and 104 were respectively monomorphic and polymorphic, an 82.54% polymorphism was established for the 10 strains evaluated. Whereas 14 out of 51 primer pairs of tested microsateilites have been selected and established a 27.4% efficiency, polymorphism for the 10 strains evaluated with 14 primers of microsateilites amounted to 52.76%. Number of alieles per microsateilite loci for the 10 popcorn strains ranged between 2 and 5, totaling 47 alieles for ali primers used. Mean number of alieles per locus was 3.36. DNA polymorphism detected for analyzed popcorn strains may be high since the proportion of polymorphic sequences was 82.54% when the 9 primers to amplify randomized sequences were used. Rate of expected mean heterozygosity was 52.76% when the 14 primers of SSR loci were employed. This fact revealed a heterozygote deficit of a mere 4.5%, coupled to a 73.49% differentiation between strains. Since Pearson?s correlation rate was 0.5453, association among markers was positive. Dendrograms made up of genotype groupings evaluation according to genetic distances and estimated from SSR loci analysis and RAPO sequences showed similar groupings which formed two great groups. In spite of the fact that there are indications that microsateilites correspond to molecular markers which are more informative than RAPD analyses, current analyses of 10 popcorn strains indicate that both techniques may provide consistent and unequivocal information for the study of genetic diversity in popcorn, coupled to an agreement in diversity rates and genetic distances.